Design, Construction and Performance Evaluation of a Mucuna Bean Seed Cracker - Etim, P. J. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
A cracking machine was developed for Mucuna bean seed. Design considerations and calculations were made using relevant equations and data from some engineering properties of the seed. A 2 hp electric motor running at a speed of 1400 rpm was used to transmit power to the gear mechanism. The cracker was fabricated using locally available materials to promote the possibility of replacing damaged parts. The performance of the machine was evaluated at various moisture levels since traditional post-harvest processing of the seed is moisture-dependent. The feed rate of the machine decreased as the moisture level increased. A significant decrease of 17.31 % was observed across the various moisture levels tested as the feed rate of the machine decreased from 8.01 to 6.59 kg/hr. At a moisture content level of 5.31 % (dry basis), the throughput capacity of the machine was obtained as 12.02 kg/hr, while between 9.14 to 11.52 % moisture content, it decreased by 3.5 %. The efficiency of cracking of the seed increased from 56.6 to 66.1 % as moisture content increased from 5.31 to 18.38 % (dry basis). The percentage of seed breakage also increased with moisture level. The seeds were observed to crack more efficiently when moisture was reduced. An average of 500 seeds were cracked within an hour, as against a minimum of 48 hours that would have been spent if the seeds were to be soaked in water before manual cracking.